Tunable plasmon resonance modes on gold nanoparticles in Er 3 +-doped germanium-tellurite glass - Rivera, V. A G; Ledemi, Y.; Osorio, S. P A; Manzani, D. [UNESP]; Ferri, F. A.; Ribeiro, Sidney J.L. [UNESP]; Nunes, L. A O; Marega, E. (Elsevier, 2013)
Relative to the Er3 +:gold-nanoparticle (Er3 +:Au-NP) axis, the polarization of the gold nanoparticle can be longitudinal (electric dipole parallel to the Er3 +:Au-NP axis) or transverse (electric dipole perpendicular to the Er3 +:Au-NP axis). For longitudinal polarization, the plasmon resonance modes of gold nanoparticles embedded in Er3 +-doped germanium-tellurite glass are activated using laser lines at 808 and 488 nm in resonance with radiative transitions of Er3 + ions. The gold nanoparticles were grown within the host glass by thermal annealing over various lengths of time, achieving diameters lower than 1.6 nm. The resonance wavelengths, determined theoretically and experimentally, are 770 and 800 nm. The absorption wavelength of nanoparticles was determined by using the Frohlich condition. Gold nanoparticles provide tunable emission resulting in a large enhancement for the 2H11/2 → 4I13/2 (emission at 805 nm) and 4S 3/2 → 4I13/2 (emission at 840 nm) electronic transitions of Er3 + ions; this is associated with the quantum yield of the energy transfer process. The excitation pathways, up-conversion and luminescence spectra of Er3 + ions are described through simplified energy level diagrams. We observed that up-conversion is favored by the excited-state absorption due to the presence of the gold nanoparticles coupled with the Er3 + ions within the glass matrix. © 2013 Elsevier B.V.
Keywords: Metallic nanoparticle; Plasmonic; Rare-earth; Tellurite glass; Absorption wavelengths; Electronic transition; Energy transfer process; Excited state absorption; Longitudinal polarization; Metallic nanoparticles; Energy transfer; Erbium; Germanium; Glass; Ions; Metal nanoparticles; Surface plasmon resonance; Tellurium compounds; Gold